The “16‐gram window” of contact‐force: A new criterion for very high‐power short‐duration ablation - Dimitrios Bismpos; Jan Wintrich; Valerie Pavlicek; Raphael Spittler; Alexander P. Benz; Michael Böhm; German Fernandez Ferro; Felix Mahfoud; Thomas Rostock; Christian Ukena (Journal of Arrhythmia, 2025)
Abstract Background Very high‐power short‐duration (vHPSD) ablation with the novel QDOT™ catheter allows the regulation of target temperature by automatically adjusting flow and power during a 4 s application of 90 W. However, the optimal contact force for sufficient lesion creation is unknown. Methods We enrolled 73 patients with symptomatic atrial fibrillation undergoing pulmonary vein isolation (PVI) using the QDOT catheter in the vHPSD mode (90 W, 4 s). Ablation metrics associated with suboptimal applications, defined as either an impedance drop of ≤5% or a cumulative temperature‐limited energy ≤330 J, were collected and analyzed. Results A total of 3881 vHPSD applications (53.2 applications per patient) with a mean contact force (CF) of 12.8 ± 6.6 g were analyzed. Significant CF variability and intermittent loss of contact were documented in 18.2% and 8.8% of the applications, respectively. A ΔImp ≤ 5% occurred in 3.9% of vHPSD applications, while a cumulative energy ≤ 330 J was observed in 3% of the applications. Applications with a mean CF < 6 g and >22 g were associated with an inadequate impedance drop (10.3%, Phi coefficient 0.118, p < .001) and total applied energy (7.8%, Phi coefficient 0.094, p < .001) respectively. At superior PV segments with thick atrial walls, significantly more applications with cumulative energy ≤330 J (4.2% vs. 2.5%; p = .007) were observed, especially when mean CF > 18 g was applied (8.4%, Phi coefficient 0.093, p = .003). Conclusion A lower but also a higher mean contact‐force was associated with suboptimal vHPSD applications. Hence, a “16‐gram window” of contact‐force, from 6 to 22 g, could optimize energy application in vHPSD ablation.